2016
DOI: 10.1007/s13205-016-0396-8
|View full text |Cite
|
Sign up to set email alerts
|

MYB transcription factor isolated from Raphanus sativus enhances anthocyanin accumulation in chrysanthemum cultivars

Abstract: A MYB transcription factor gene, RsMYB1, from radish was introduced into the chrysanthemum cultivars ‘Peach ND’, ‘Peach Red’, and ‘Vivid Scarlet’ under the control of the cauliflower mosaic virus 35S promoter. Presence of RsMYB1 in transgenic lines was confirmed using polymerase chain reaction (PCR). Results of reverse-transcription-PCR analysis revealed that the expression of RsMYB1 was stable in all transgenic lines and could enhance the expression levels of three key biosynthetic genes (F3H, DFR, and ANS) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…4b)]. These results are in agreement with the findings of Ai et al (2016aAi et al ( , 2017 and Kee et al (2016), who also observed differential expression of the same TFs in independent transgenic petunia and chrysanthemum lines. Interestingly, the transcript levels of the TFs were not directly correlated with transcriptional activation of the structural genes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…4b)]. These results are in agreement with the findings of Ai et al (2016aAi et al ( , 2017 and Kee et al (2016), who also observed differential expression of the same TFs in independent transgenic petunia and chrysanthemum lines. Interestingly, the transcript levels of the TFs were not directly correlated with transcriptional activation of the structural genes.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, enhancement of anthocyanin production in ornamental crops by TF overexpression is well-documented (Zvi et al 2012;Albert et al 2014;Cavallini et al 2014;Schwinn et al 2014;Naing et al 2018). Increased expression of anthocyanin structural genes, which are involved in anthocyanin production, via overexpression of RsMYB1 in different chrysanthemum cultivars has been reported (Naing et al 2015;Kee et al 2016). Moreover, overexpression of RsMYB1 or mPAP1 + B-Peru in petunia was also found to enhance anthocyanin pigmentation in vegetative and floral tissues by elevating the transcript levels of structural genes (Ai et al 2016a(Ai et al , 2017.…”
Section: Discussionmentioning
confidence: 96%
“…Alterations in floral color and petal pigmentation patterns are regulated by changes in the expression of anthocyanin biosynthetic genes. Although transgenic chrysanthemum overexpressing MYB1 from Raphanus sativus showed increased expression of anthocyanin biosynthetic genes F3H , DFR , and ANS , and anthocyanin accumulation, there was no visual increase in floral color in the transgenic plants [ 61 ]. The Chrysanthemum genus does not synthesize delphinidin-based anthocyanins naturally because of the absence of F3′5′H ; hence, blue-colored flowers are absent in chrysanthemum.…”
Section: Floral Colormentioning
confidence: 99%
“…Additionally, CmMYB6 alone activated the CmDFR gene and induced anthocyanin biosynthesis in tobacco leaves when transiently co-expressed with a previously characterized anthocyanin regulator, MrbHLH1 [ 72 ]. Transgenic chrysanthemum expressing RsMYB1 presented enhanced accumulation due to the upregulation of CmF3H , CmDFR , and CmANS [ 73 ]. Recently, R3 MYB, CmMYB#7 was identified as a passive repressor of anthocyanin biosynthesis [ 74 ].…”
Section: Regulation Of Anthocyanin Biosynthesis By Transcription Fmentioning
confidence: 99%
“…Kee et al developed a transgenic chrysanthemum overexpressing RsMYB1 , in which the expression of three anthocyanin biosynthetic genes, such as F3H , DFR , and ANS , was elevated. However, there was no visual enhancement of anthocyanin in the transgenic plants [ 73 ]. Members of the family Asteraceae, such as cineraria and African daisy , can accumulate delphinidin-based anthocyanins in their flowers due to the activity of F3′5′H [ 166 ].…”
Section: Breeding For Anthocyaninsmentioning
confidence: 99%